A biodegradable, sustained-released, prednisolone acetate microfilm drug delivery system effectively prolongs corneal allograft survival in the rat keratoplasty model - Liu, Yu-Chi (2013)
Frequent and long-term use of topical corticosteroids after corneal transplantation is necessary to prevent graft rejection. However, it relies heavily on patient compliance, and sustained therapeutic drug levels are often not achieved with administration of topical eye drops. A biodegradable drug delivery system with a controlled and sustained drug release may circumvent these limitations. In this study, we investigated the efficacy of a prednisolone acetate (PA)-loaded poly (d,l-lactide-co-ε-caprolactone) (PLC) microfilm drug delivery system on promoting the survival of allogeneic grafts after penetrating keratoplasty (PK) using a rat model. The drug release profiles of the microfilms were characterized (group 1). Subsequently, forty-eight PK were performed in four experimental groups: syngeneic control grafts (group 2), allogeneic control grafts (group 3), allogeneic grafts with subconjunctivally-implanted PA microfilm (group 4), and allogeneic grafts with PA eye drops (group 5; n = 12 in each). PA-loaded microfilm achieved a sustained and steady release at a rate of 0.006–0.009 mg/day, with a consistent aqueous drug concentration of 207–209 ng/ml. The mean survival days was >28 days in group 2, 9.9±0.8 days in group 3, 26.8±2.7 days in group 4, and 26.4±3.4 days in group 5 (P = 0.023 and P = 0.027 compared with group 3). Statistically significant decrease in CD4+, CD163+, CD 25+, and CD54+ cell infiltration was observed in group 4 and group 5 compared with group 3 (P<0.001). There was no significant difference in the mean survival and immunohistochemical analysis between group 4 and group 5. These results showed that sustained PA-loaded microfilm effectively prolongs corneal allograft survival. It is as effective as conventional PA eye drops, providing a promising clinically applicable alternative for patients undergoing corneal transplantation.